Multi-focus auto focusing characteristics of vector beam with non-uniformly correlated structure in a turbulent atmosphere - Yang, Xianyang; Fu, Wenyu; Zhu, Xiaolu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
We propose a simple strategy to produce multiple longitudinal focal spots by adjusting the initial parameters of vector beam with non-uniformly correlated structure and chose electromagnetic Hermite non-uniformly correlated (EMHNUC) beams as typical examples to explore the multi-focusing characteristics of the beam propagation in turbulent atmosphere. Furthermore, we also demonstrated how to control the foci’s number, intensity, and position by adjusting the vector beam’s initial parameters. Finally, the influence of the turbulent atmosphere on the focal spot intensity was analyzed. These beams may prove helpful in longitudinal optical trapping and manipulation of multiple particles and transparent material cutting.
Optica Applicata, Vol. 54, 2024, nr 4, s. 459-469
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; electromagnetic Hermite non-uniformly beams; multi-focusing characteristics; turbulent atmosphere